Diaphragm and device comprising same
By using a combined structure of porous substrate and porous coating in the separator of the electrochemical device, the problem of insufficient safety of the existing electrochemical device in extreme environments is solved, and the high temperature stability and mechanical safety performance of the separator are significantly improved.
Patent Information
- Application Number
- CN202510139833.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-24
- Publication Date
- 2025-03-21
AI Technical Summary
Existing electrochemical devices are difficult to ensure safety in extreme environments, especially in high temperature, impact and hot box environments, which are prone to dangers such as fire and explosion.
By improving the separator of the electrochemical device, a combined structure of a porous substrate and a porous coating is employed, wherein the porous coating comprises inorganic particles and a binder that contains metal elements to improve the modulus and stability of the separator.
The improved diaphragm has excellent high temperature resistance, heat shrinkage resistance, heat puncture, heat box performance and cycle stability, which significantly improves the safety performance of electrochemical devices in extreme environments.
Smart Images

Figure CN119674449A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent with application number 202280004833.8 (international application number: PCT / CN2022 / 088842) filed on April 24, 2022, whose invention name is "Diaphragm and device containing the same". Technical Field
[0002] The present application relates to the field of energy storage technology, and more specifically, to a diaphragm and a device comprising the same. Background Art
[0003] Rechargeable electrochemical devices (such as lithium-ion batteries and sodium-ion batteries) are considered to be one of the most attractive energy storage systems due to their high energy density, relatively simple reaction mechanism, high operating voltage, long life, and green environmental protection. Nowadays, electrochemical devices have been widely used in various fields such as wearable devices, smart phones, drones, and laptops.
[0004] With the widespread application of electrochemical devices in various fields, people have higher and higher requirements for electrochemical devices. For example, sometimes, when electrochemical devices work or are abused in some extreme environments (such as impact, nail penetration, and hot boxes), people still need electrochemical devices to work safely without fire, explosion, and other dangers. However, the electrochemical devices in the existing technology are difficult to meet the above requirements. In view of this, it is urgent to improve the safety performance of electrochemical devices, especially to improve the safety performance of electrochemical devices in extreme environments. Summary of the invention
[0005] At least to solve the above problems, the present application improves the safety performance of the electrochemical device by improving the diaphragm of the electrochemical device. Specifically, the present application provides a diaphragm with high safety performance, which has excellent high temperature resistance, heat shrinkage resistance, thermal puncture resistance, hot box performance and cycle stability.
[0006] According to one aspect of the present application, the present application provides a membrane, comprising: a porous substrate and a porous coating, wherein the porous coating is disposed on at least one surface of the porous substrate, the porous coating comprises inorganic particles and a binder, the binder comprises a first binder, the first binder comprises a metal element, wherein the modulus of the membrane at a temperature T is P, 100°C ≤ T ≤ 180°C, 10 8 Pa≤P≤10 9 Pa.
[0007] According to an embodiment of the present application, the tensile strength of the adhesive is αMPa, 0.5≤α≤30.
[0008] According to an embodiment of the present application, the melting temperature of the binder is T f ℃, 150≤T f ≤250.
[0009] According to an embodiment of the present application, the metal element includes at least one of metal elements with a valence of +1, +2 or +3.
[0010] According to an embodiment of the present application, the adhesive further includes a second adhesive.
[0011] According to an embodiment of the present application, the binder satisfies one of the following conditions: (a) based on the total weight of the porous coating, the weight contents of the first binder and the second binder are w1% and w2%, respectively, wherein 0.2≤w1≤4, 2≤w2≤8, and 0.025≤w1 / w2≤2; (b) the pH value of the first binder is pH1, the pH value of the second binder is pH2, 7≤pH1≤11, 3≤pH2≤7, and 1≤pH1 / pH2≤3.6.
[0012] According to an embodiment of the present application, the second binder satisfies one of the following conditions: (c) based on the total weight of the porous coating, the weight content w2% of the second binder satisfies 2≤w2≤8; (d) the pH value pH2 of the second binder satisfies 3≤pH2≤7.
[0013] According to an embodiment of the present application, the first binder satisfies one of the following conditions: (e) the first binder contains only the metal element with a valence of +1 and the metal element with a valence of +2, wherein the molar content ratio of the metal element with a valence of +1 to the metal element with a valence of +2 is a, 1≤a≤10; or (f) the first binder contains only the metal element with a valence of +1 and the metal element with a valence of +3, wherein the molar content ratio of the metal element with a valence of +1 to the metal element with a valence of +3 is b, 1≤b≤50.
[0014] According to an embodiment of the present application, the metal elements include at least two of Li, Na, Ca, Mg or Al.
[0015] According to an embodiment of the present application, at least one of the first binder and the second binder includes a carboxyl group and / or a sulfonic acid group.
[0016] According to an embodiment of the present application, the binder satisfies at least one of the following conditions: (g) the first binder includes at least one of the following: sodium polymethylcellulose, lithium polymethylcellulose, lithium polycarboxymethylcellulose, lithium polyhydroxypropyl methylcellulose, calcium polyacrylate, lithium polyacrylate or calcium polymethacrylate; or (h) the second binder includes at least one of the following: polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate or styrene-butadiene rubber.
[0017] According to an embodiment of the present application, the specific surface area of the inorganic particles is S BET m 2 / g,2≤S BET ≤10.
[0018] According to an embodiment of the present application, the median particle size Dv50 of the inorganic particles satisfies 0.3 μm≤Dv50≤2 μm.
[0019] According to an embodiment of the present application, the inorganic particles include at least one of the following: aluminum oxide, boehmite, zirconium oxide, boron nitride, silicon nitride or aluminum nitride.
[0020] According to an embodiment of the present application, the porous coating further includes a wetting agent, wherein, based on the total weight of the porous coating, the weight content of the inorganic particles is m1%, the weight content of the binder is m2%, and the weight content of the wetting agent is m3%, wherein 90≤m1≤96, 3≤m2≤9, 0.5≤m3≤1.5, and m1+m2+m3=100.
[0021] According to an embodiment of the present application, the wetting agent includes at least one of the following: polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer or siloxane.
[0022] According to an embodiment of the present application, the diaphragm is placed at 150°C for 1 hour, the thermal shrinkage rate of the diaphragm in the MD direction is L1, and the thermal shrinkage rate in the TD direction is L2, L1<10%, L2<10%, 0.75≤L1 / L2≤1.2.
[0023] According to an embodiment of the present application, the diaphragm satisfies at least one of the following conditions: (i) the thickness of the diaphragm is Hμm, 3.5≤H≤14; (j) the thickness of the porous substrate is H1μm, 3≤H1≤10; or (k) the thickness of the porous coating is H2μm, 0.5≤H2≤4.
[0024] According to an embodiment of the present application, the porous coating satisfies at least one of the following conditions: (1) the adhesion of the porous coating is FN / m, 5≤F≤100; (2) the air permeability of the porous coating is Ks / 100ml, 5≤K≤40.
[0025] According to another aspect of the present application, the present application also provides an electrochemical device, which includes the diaphragm described in the above embodiment of the present application.
[0026] According to another aspect of the present application, the present application also provides an electronic device, which includes the electrochemical device described in the above embodiment of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some of the embodiments in the present application. For those skilled in the art, without the need for creative work, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.
[0028] Figure 1 The morphology of the separator described in the example of the present application after being baked at 150° C. for 1 hour is shown, wherein the initial length (MD) and width (TD) of the separator are 10 cm and 5 cm, respectively.
[0029] Figure 2 The figure shows the morphology of a separator in the prior art after being baked at 150° C. for 1 hour, wherein the initial length (MD) and width (TD) of the separator are 10 cm and 5 cm, respectively. DETAILED DESCRIPTION
[0030] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0031] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.
[0032] In addition, sometimes amounts, ratios and other numerical values are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values explicitly specified as range limits, but also all individual numerical values or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.
[0033] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0034] Diaphragm
[0035] As an important component of an electrochemical device, the diaphragm is located between the positive and negative electrodes of the electrochemical device to isolate the positive and negative electrodes while transmitting metal ions (e.g., lithium ions) to prevent short circuits. However, when used abnormally or abused, the temperature inside the electrode assembly of the electrochemical device may rise sharply, causing the diaphragm to shrink to a large extent or even melt, resulting in direct contact between the positive and negative electrodes and a short circuit. Once a short circuit occurs, thermal runaway will occur inside the electrochemical device, resulting in safety issues such as fire and explosion.
[0036] The prior art usually uses an oily diaphragm (e.g., an aramid high temperature resistant diaphragm) in an electrochemical device to improve the diaphragm's tolerance to high temperatures. However, the oily diaphragm has high requirements for the production process and can cause environmental pollution and other problems. In addition, compared to water-based diaphragms, the production cost of oily diaphragms is higher, which will increase the production cost of electrochemical devices accordingly.
[0037] At least based on the above insights into the prior art, the present application takes water-based diaphragms as the research object, and improves the thermal stability and mechanical safety performance of the diaphragm by improving the composition and content of the porous coating in the diaphragm. Specifically, the diaphragm proposed in the present application includes a porous substrate and a porous coating, and the porous coating is arranged on at least one surface of the porous substrate, wherein the porous coating includes inorganic particles and a binder. A main feature of the diaphragm of the present application is that the binder includes a first binder, and the first binder includes a metal element, and the diaphragm has a very high modulus at high temperature. For example, the modulus of the diaphragm described in the present application at temperature T is P, 100℃≤T≤180℃, 10 8 Pa≤P≤10 9Pa. In comparison, the maximum modulus of the diaphragm in the prior art (e.g., the diaphragm of Comparative Example 1-1) in the temperature range of 100°C to 180°C can only reach 9211891 Pa. This shows that the diaphragm described in the present application has good thermal stability and mechanical stability at high temperatures.
[0038] in addition, Figure 1 and Figure 2 The morphology of the diaphragm in one embodiment of the present application and the diaphragm in the prior art after being baked at 150° C. for 1 hour is shown respectively. Figure 1 As shown in the figure, after being baked at 150°C for 1 hour, at the macro level, the separator described in the present application becomes transparent, has a smooth surface, and has no inorganic particles falling off; at the micro level, the cross section of the separator observed by scanning electron microscopy shows that the porous coating is integrated with the substrate, the substrate melts at 150°C, and the pores between the inorganic particles in the porous coating are also filled with the melted substrate polymer. In contrast, Figure 2 As shown, the diaphragm in the prior art undergoes severe thermal shrinkage after being baked at 150° C. for 1 hour, and a large amount of inorganic particles fall off from the substrate.
[0039] In some embodiments, the modulus of the membrane described in the present application is related to the modulus of the binder, wherein the modulus of the binder can be changed by adjusting factors such as the component, content, pH value, etc. of the binder used, thereby adjusting the modulus P of the membrane at high temperature.
[0040] In some embodiments, the tensile strength of the binder is αMPa, where 0.5≤α≤30. When the tensile strength of the binder is within the above range, the binder can not only firmly connect the dispersed inorganic particles into a network skeleton structure, but also bond the inorganic particles to the substrate to form a whole, thereby ultimately improving the tensile strength of the entire diaphragm, so that the diaphragm can better resist stress shock, further inhibit damage caused by shock, and further improve the thermal safety and mechanical safety of the electrochemical device. In some embodiments, α can be, but is not limited to, 0.5, 5, 10, 15, 20, 25 or 30, or within the range of any two of the above values.
[0041] In some embodiments, the melting temperature of the binder is T f ℃, where 150≤T f ≤250. When the melting temperature of the binder is within the above range, the bonding structure formed by the binder can have an appropriate strength at high temperature to better resist stress impact and reduce damage caused by impact, thereby further improving the thermal safety and mechanical safety of the electrochemical device. In some embodiments, T fIt can be, but is not limited to, 150, 175, 200, 225 or 250, or within the range formed by any two of the above values.
[0042] In some embodiments, the metal element in the first binder includes at least one of the metal elements with a valence of +1, +2 or +3. In some embodiments, the first binder also includes at least one of a carboxyl group or a sulfonic acid group. The metal ions in the first binder can be complexed with the carboxyl group or the sulfonic acid group therein to form a metal bond, further improving the strength (e.g., tensile strength) of the binder, so that the diaphragm can better cope with stress shocks, inhibit damage / contraction caused by shocks, thereby further improving the thermal safety and mechanical safety performance of the electrochemical device.
[0043] In some embodiments, the metal element with a valence of +1 includes at least one of Li, Na, or K. In some embodiments, the metal element with a valence of +2 includes at least one of Ca, Mg, or Ba. In some embodiments, the metal element with a valence of +3 includes Al. In some embodiments, the first binder includes at least one of Li, Na, Ca, Mg, or Al.
[0044] In some embodiments, the binder includes both a first binder and a second binder. In some embodiments, the first binder and the second binder are different types of binders. For example, the first binder is a solution-type binder. A solution-type binder refers to a binder polymer dissolved in a solvent to form a solution. In some embodiments, the solvent is water. The second binder is an emulsion binder. An emulsion binder refers to a binder polymer dispersed in a dispersion medium to form an emulsion. In some embodiments, the dispersion medium is water.
[0045] In some embodiments, the functional group of the second binder includes at least one of a carboxyl group or a sulfonic acid group. When the binder includes both the first binder and the second binder, the metal ions in the first binder can be complexed with the carboxyl group or the sulfonic acid group in the second binder to form a metal bond and an interpenetrating network structure, thereby further improving the strength of the binder and the ability of the diaphragm to resist external impact, thereby further improving the thermal safety and mechanical safety of the electrochemical device.
[0046] In addition, when the binder includes both the first binder and the second binder, the strength of the binder can be further improved by optimizing the content and ratio of the first binder and the second binder. In some embodiments, based on the total weight of the porous coating, the weight content of the first binder is w1%, where 0.2≤w1≤4. In some embodiments, w1 can be, but is not limited to, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5 or 4, or within the range of any two of the above values.
[0047] In some embodiments, based on the total weight of the porous coating, the weight content of the second binder is w2%, wherein 2≤w2≤8. In some embodiments, w2 can be, but is not limited to, 2, 3, 4, 5, 6, 7 or 8, or within a range consisting of any two of the above values.
[0048] In some embodiments, the content ratio of the first binder to the second binder (ie, w1 / w2) is 0.025≤w i / w2≤2. In some embodiments, w1 / w2 may be, but is not limited to, 0.025, 0.05, 0.1, 0.5, 1, 1.5 or 2, or within the range of any two of the above values.
[0049] In some embodiments, the pH value of the first binder can be adjusted by adjusting the content and ratio of the carboxyl or sulfonic acid group and the metal element in the first binder. In some embodiments, the pH value of the first binder is pH1, 7≤pH1≤11. When the pH value of the first binder is within the above range, the first binder contains an excess of metal ions that are not complexed with the carboxyl or sulfonic acid groups therein, and these remaining metal ions can further complex with the carboxyl or sulfonic acid groups in the second binder, thereby increasing the bonding strength of the binder to further improve the thermal stability and mechanical properties of the diaphragm. In some embodiments, pH1 can be, but is not limited to, 7, 8, 9, 10 or 11, or within the range of any two of the above values.
[0050] In some embodiments, the pH value of the second binder can be adjusted by adjusting the content and ratio of the carboxyl and / or sulfonic acid groups in the second binder. In some embodiments, the pH value of the second binder is pH2, 3≤pH2≤7. When the pH value of the second binder is within the above range, a large number of carboxyl and / or sulfonic acid groups can be provided to complex with the metal ions in the first binder, improve the mechanical properties of the binder to further improve the thermal stability and mechanical properties of the diaphragm. In some embodiments, pH2 can be, but is not limited to, 3, 4, 5, 6 or 7, or within the range of any two of the above values.
[0051] In some embodiments, the thermal stability and mechanical properties of the diaphragm can be further improved by adjusting the pH values of the first binder and the second binder to satisfy 1≤pH1 / pH2≤3.6. In some embodiments, pH1 / pH2 can be, but is not limited to, 1, 1.5, 2, 2.5, 3 or 3.6, or within the range of any two of the above values.
[0052] In some embodiments, the second binder satisfies one of the following conditions: based on the total weight of the porous coating layer, a weight content w2% of the second binder satisfies 2≤w2≤8; or a pH value pH2 of the second binder satisfies 3≤pH2≤7.
[0053] In some embodiments, the metal element in the first binder includes at least two of the metal elements with a valence of +1, +2 or +3. Compared with containing only one metal element, using at least two different metal elements in the first binder can further enhance the strength of the binder, thereby further improving the ability of the diaphragm to cope with stress shocks and its stability at high temperatures. This may be because compared with a single metal element, different metal elements are more likely to form interpenetrating metal bonds with carboxyl and / or sulfonic acid groups in the binder to construct an interpenetrating cross-linked network structure, thereby improving the mechanical properties of the material.
[0054] In some embodiments, the metal element in the first binder includes at least two metal elements with different valences among metal elements with valences of +1, +2 or +3. Compared with different metal elements with the same valence, when the first binder contains metal elements with different valences, it is easier to form interpenetrating metal bonds with the carboxyl group and / or sulfonic acid group in the binder to construct an interpenetrating cross-linked network structure, thereby improving the mechanical properties of the material.
[0055] In some embodiments, the first binder includes only metal elements with valences of +1 and +2, wherein the molar content ratio of the metal element with a valence of +1 to the metal element with a valence of +2 is a, 1≤a≤10. In some embodiments, a can be, but is not limited to, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, or is within the range of any two of the above values.
[0056] In some embodiments, the first binder includes only metal elements with valences of +1 and +3, wherein the molar content ratio of the metal element with a valence of +1 to the metal element with a valence of +3 is b, 1≤b≤50. In some embodiments, b can be, but is not limited to, 1, 10, 20, 30, 40 or 50, or is within the range of any two of the above values.
[0057] In some embodiments, the first binder includes only metal elements with valences of +2 and +3, wherein the molar content ratio of the metal element with a valence of +2 to the metal element with a valence of +3 is c, 1≤c≤10. In some embodiments, c can be, but is not limited to, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, or is within the range of any two of the above values.
[0058] In some embodiments, the metal element in the first binder includes at least two of Li, Na, Ca, Mg, or Al.
[0059] In some embodiments, the first binder satisfies at least one of the following conditions:
[0060] (1) The first binder includes Li and Na at the same time, wherein the molar content ratio of Li to Na is d, 1≤d≤8;
[0061] (2) The first binder includes Li and Mg at the same time, wherein the molar content ratio of Li to Mg is e, 2≤e≤4;
[0062] (3) The first binder includes Na and Mg at the same time, wherein the molar content ratio of Na to Mg is f, 2≤f≤4;
[0063] (4) The first binder includes Li and Ca at the same time, wherein the molar content ratio of Li to Ca is g, 2≤g≤4;
[0064] (5) The first binder includes Na and Ca at the same time, wherein the molar content ratio of Na to Ca is m, 2≤m≤4;
[0065] (6) The first binder includes Li and Al at the same time, wherein the molar content ratio of Li to Al is n, 1≤n≤20;
[0066] (7) The first binder includes Na and Al at the same time, wherein the molar content ratio of Na to Al is p, 1≤p≤20.
[0067] In some embodiments, the first binder includes, but is not limited to, at least one of sodium polymethylcellulose, lithium polymethylcellulose, lithium polycarboxymethylcellulose, lithium polyhydroxypropylmethylcellulose, calcium polyacrylate, lithium polyacrylate, or calcium polymethacrylate.
[0068] In some embodiments, the second binder includes, but is not limited to, at least one of: polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate, or styrene-butadiene rubber.
[0069] In some embodiments, the specific surface area of the inorganic particles in the porous coating is S BET m 2 / g,2≤S BET ≤10. In some embodiments, S BET It can be, but is not limited to, 2, 3, 4, 5, 6, 7, 8, 9 or 10, or within the range of any two of the above values. In some embodiments, 2≤S BET ≤5.
[0070] In some embodiments, the median particle size Dv50 of the inorganic particles satisfies 0.3 μm ≤ Dv50 ≤ 2 μm, where Dv50 is the particle size value corresponding to 50% of the volume distribution. When the particle size of the inorganic particles is within the above range, it is beneficial to reduce the thickness of the porous coating and improve the energy density of the electrochemical device, and it can also ensure that the bonding site is within a suitable range, reduce the amount of binder, and improve the kinetic performance of the electrochemical device.
[0071] In some embodiments, the inorganic particles that can be used in the separator of the present application include, but are not limited to, at least one of the following: aluminum oxide, boehmite, zirconium oxide, boron nitride, silicon nitride, aluminum nitride, silicon dioxide, magnesium oxide, titanium oxide, silicon carbide, aluminum hydroxide, or magnesium hydroxide.
[0072] In some embodiments, the porous coating further includes a wetting agent, wherein the role of the wetting agent is to improve the wettability of the porous coating slurry to the substrate to avoid leaking during the coating process. In addition, by optimizing the weight proportion of inorganic particles, binders and wetting agents in the porous coating, the thermal safety performance and mechanical stability of the diaphragm can be further enhanced. In some embodiments, based on the total weight of the porous coating, the weight content of the inorganic particles is m1%, the weight content of the binder is m2%, and the weight content of the wetting agent is m3%, wherein 90≤m1≤96, 3≤m2≤9, 0.5≤m3≤1.5, and m1+m2+m3=100.
[0073] In some embodiments, the wetting agent includes, but is not limited to, at least one of the following: polyoxyethylene alkylphenol ethers, polyoxyethylene fatty alcohol ethers, polyoxyethylene polyoxypropylene block copolymers, or siloxanes.
[0074] In some embodiments, the membrane of the present application is placed at 150°C for 1 hour. Compared with the initial length of the membrane, the thermal shrinkage rate of the membrane in the length (MD) direction is L1, and compared with the initial width of the membrane, the thermal shrinkage rate of the membrane in the width (TD) direction is L2, wherein L1<10%, L2<10%, 0.75≤L1 / L2≤1.2. In some embodiments, L1 and L2 can be, but not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, or 9%, respectively, or within the range of any two of the above values. In some embodiments, L1 / L2 can be, but not limited to, 0.8, 0.9, 1.0, 1.1 or 1.2, or within the range of any two of the above values.
[0075] In some embodiments, the thickness of the membrane described in the present application is H μm, wherein 3.5≤H≤14. In some embodiments, H may be, but is not limited to, 3.5, 5, 7, 9, 10, 12 or 14, or within a range consisting of any two of the above values.
[0076] In some embodiments, the porous substrate described in the present application may include, but is not limited to, at least one of the following: polyethylene (PE), ultra-high molecular weight polyethylene (UHMWPE), high-density polyethylene (HDPE), polypropylene (PP), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), cellulose, polyimide, polystyrene (PS), poly-4-methyl-1-pentene (TPX), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE) and polysulfone.
[0077] In some embodiments, the porous substrate described herein has a thickness of H1 μm, wherein 3≤H1≤10. In some embodiments, H1 may be, but is not limited to, 3, 4, 5, 6, 7, 8, 9 or 10, or within a range consisting of any two of the above values.
[0078] In some embodiments, the thickness of the porous coating described in the present application is H2 μm, wherein 0.5 ≤ H2 ≤ 4. When the thickness of the porous coating is within the above range, it can not only improve the energy density of the electrochemical device, but also improve the kinetic performance of the electrochemical device. In some embodiments, H2 can be, but is not limited to, 0.5, 1, 1.5, 2, 2.5, 3, 3.5 or 4, or within a range consisting of any two of the above values. Wherein, when a porous coating is coated on both surfaces of the porous substrate, the above-mentioned "thickness of the porous coating" refers to the sum of the thicknesses of the porous coatings coated on the two surfaces.
[0079] In some embodiments, the bonding force of the porous coating is FN / m, 5≤F≤100. When the bonding force of the porous coating is within the above range, not only can the inorganic particles be firmly bonded to the porous substrate without being easily detached, but also it is not necessary to use too much binder to deteriorate the kinetic performance of the electrochemical device. In some embodiments, F can be, but is not limited to, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, or within the range consisting of any two of the above values. In some embodiments, 20≤F≤85.
[0080] In some embodiments, the porous coating has an air permeability of K s / 100 ml, 5≤K≤40. In some embodiments, K may be, but is not limited to, 5, 10, 15, 20, 25, 30, 35 or 40, or within a range consisting of any two of the foregoing values.
[0081] The present application further provides an electrochemical device, which includes the separator of the above embodiment of the present application. In some embodiments, the electrochemical device further includes a negative electrode, a positive electrode and an electrolyte, wherein the separator is located between the positive electrode and the negative electrode. As follows, the present application will describe in detail the composition of the positive electrode, the negative electrode and the electrolyte.
[0082] positive electrode
[0083] The positive electrode includes a positive electrode material, and the positive electrode material includes a positive electrode material capable of absorbing and releasing lithium (Li) (hereinafter, sometimes referred to as "a positive electrode material capable of absorbing / releasing lithium Li"). Examples of the positive electrode material capable of absorbing / releasing lithium (Li) may include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium titanate, and lithium-rich manganese-based materials.
[0084] Specifically, the chemical formula of lithium cobalt oxide may be as shown in Chemical Formula 1:
[0085] Li x1 Co a1 M1 b1 O 2-c1 Chemical formula 1
[0086] Wherein M1 represents at least one selected from nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), yttrium (Y), lanthanum (La), zirconium (Zr) and silicon (Si), and the values of x1, a1, b1 and c1 are respectively in the following ranges: 0.8≤x1≤1.2, 0.8≤a1≤1, 0≤b1≤0.2, -0.1≤c1≤0.2;
[0087] The chemical formula of lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide may be as shown in Chemical Formula 2:
[0088] Li y1 Ni d1 M2 e1 O 2-f1 Chemical formula 2
[0089] Wherein M2 represents at least one selected from cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), zirconium (Zr) and silicon (Si), and the values of y1, d1, e1 and f1 are respectively in the following ranges: 0.8≤y1≤1.2, 0.3≤d1≤0.98, 0.02≤e1≤0.7, -0.1≤f1≤0.2;
[0090] The chemical formula of lithium manganate can be as shown in Chemical Formula 3:
[0091] Li z1 Mn 2-g1 M 3g1 O 4-h1 Chemical formula 3
[0092] Wherein M3 represents at least one selected from cobalt (Co), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr) and tungsten (W), and the values of z1, g1 and h1 are respectively in the following ranges: 0.8≤z1≤1.2, 0≤g1≤1.0 and -0.2≤h1≤0.2.
[0093] negative electrode
[0094] The negative electrode includes a negative electrode material, and the negative electrode material includes a negative electrode material capable of absorbing and releasing lithium (Li) (hereinafter, sometimes referred to as "a negative electrode material capable of absorbing / releasing lithium Li"). Examples of the negative electrode material capable of absorbing / releasing lithium (Li) may include carbon materials, metal compounds, oxides, sulfides, lithium nitrides such as LiN3, lithium metal, metals that form alloys with lithium, and polymer materials.
[0095] The example of carbon material can comprise low graphitized carbon, easy graphitized carbon, artificial graphite, natural graphite, mesophase carbon microsphere, soft carbon, hard carbon, pyrolytic carbon, coke, glassy carbon, organic polymer compound sintered body, carbon fiber and activated carbon. Wherein, coke can comprise pitch coke, needle coke and petroleum coke. Organic polymer compound sintered body refers to the material obtained by calcining polymer material such as phenol plastic or furan resin at appropriate temperature so that carbonization, some of these materials are divided into low graphitized carbon or easy graphitized carbon. The example of polymer material can comprise polyacetylene and polypyrrole.
[0096] Among these negative electrode materials capable of absorbing / releasing lithium (Li), further, materials having a charge and discharge voltage close to that of lithium metal are selected. This is because the lower the charge and discharge voltage of the negative electrode material, the easier it is for an electrochemical device (such as a lithium ion battery) to have a higher energy density. Among them, carbon materials can be selected as negative electrode materials because their crystal structures change only slightly during charge and discharge, and therefore, good cycle characteristics and large charge and discharge capacities can be obtained. Graphite can be selected in particular because it can give a large electrochemical equivalent and a high energy density.
[0097] In addition, the negative electrode material capable of absorbing / releasing lithium (Li) may include single substance lithium metal, metal elements and semi-metal elements capable of forming alloys with lithium (Li), alloys and compounds of such elements, etc. In particular, they are used together with carbon materials, because in this case, good cycle characteristics and high energy density can be obtained. In addition to alloys including two or more metal elements, the alloys used here also include alloys containing one or more metal elements and one or more semi-metal elements. The alloy may be in the following states: solid solution, eutectic crystal (eutectic mixture), intermetallic compound and mixture thereof.
[0098] Examples of metal elements and semi-metal elements may include tin (Sn), lead (Pb), aluminum (Al), indium (In), silicon (Si), zinc (Zn), antimony (Sb), bismuth (Bi), cadmium (Cd), magnesium (Mg), boron (B), gallium (Ga), germanium (Ge), arsenic (As), silver (Ag), zirconium (Zr), yttrium (Y) and hafnium (Hf). Examples of the above alloys and compounds may include materials having the chemical formula: MasMbtLiu and materials having the chemical formula: MapMcqMdr. In these chemical formulas, Ma represents at least one element of metal elements and semi-metal elements that can form an alloy with lithium; Mb represents at least one element of metal elements and semi-metal elements other than lithium and Ma; Mc represents at least one element of non-metal elements; Md represents at least one element of metal elements and semi-metal elements other than Ma; and s, t, u, p, q and r satisfy s>0, t≥0, u≥0, p>0, q>0 and r>0.
[0099] In addition, inorganic compounds that do not include lithium (Li), such as MnO2, V2O5, V6O 13 , NiS and MoS.
[0100] Electrolytes
[0101] The electrolyte may be one or more of a gel electrolyte, a solid electrolyte and an electrolyte solution, wherein the electrolyte solution includes a lithium salt and a non-aqueous solvent.
[0102] The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB and lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics.
[0103] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.
[0104] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.
[0105] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methylethyl carbonate (MEC), and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), and combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof.
[0106] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, and combinations thereof.
[0107] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.
[0108] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters and combinations thereof.
[0109] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0110] The present application further provides an electronic device, which includes the electrochemical device according to the present application.
[0111] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0112] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.
[0113] Example
[0114] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.
[0115] 1. Preparation of lithium-ion batteries
[0116] 1. Preparation of binder
[0117] The preparation process of acrylic adhesive is as follows: 1. Add an appropriate amount of acrylic acid monomer into a reactor, add an appropriate amount of catalyst, and stir slowly and evenly; 2. Add an appropriate amount of sulfonic acid monomer or carboxyl monomer (for example, methylpropanesulfonic acid or methacrylic acid) into the reactor; 3. Inert gas is introduced into the reactor to form a reaction protective atmosphere; 4. The reactor is heated to the reaction temperature, and the monomers are polymerized to obtain an adhesive containing two functional groups at the same time; 5. After the reaction is completed, a metal base can be added to adjust the pH of the adhesive output to obtain the desired adhesive.
[0118] By changing the type of reactive monomer, a binder containing different functional groups can be obtained. By selecting different types of metal bases (e.g., sodium hydroxide, magnesium hydroxide) or adding different amounts of metal bases, the type and content ratio of the metal base in the binder can be designed and regulated.
[0119] The preparation process of cellulose binder is as follows: 1. Place an appropriate amount of raw cellulose in a reaction kettle, then add a metal base (sodium hydroxide) to alkalize the cellulose to obtain alkalized cellulose; 2. Add an appropriate amount of chloroacetic acid to the alkalized cellulose to carry out an etherification reaction, and finally obtain a sodium cellulose binder.
[0120] Among them, during the alkalization treatment process, the type and content ratio of the metal base in the binder can be designed and regulated by changing relevant process parameters such as the type of metal base or the ratio of metal base.
[0121] 2. Preparation method of diaphragm
[0122] After the water and inorganic particles are fully mixed, a certain amount of adhesive is added, and the mixture is placed in a stirrer and stirred evenly. Subsequently, a certain amount of wetting agent is added to the above slurry, and stirring is continued until the mixture is evenly mixed. Finally, the substrate PE side is evenly coated to a suitable thickness, and after the coating is completed, it is placed in an oven and dried to obtain the diaphragm of the present application. The composition and content of the inorganic particles, adhesive and wetting agent, and the coating thickness and other parameters are shown in Table 1.
[0123] 3. Preparation method of lithium-ion battery
[0124] The positive electrode active material lithium cobalt oxide, conductive carbon (Super P) and binder polyvinylidene fluoride (PVDF) are dissolved in an N-methylpyrrolidone solvent system at a weight ratio of 96:2:2, and stirred and mixed to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil, dried, cold pressed, and slit to obtain a positive electrode.
[0125] The negative electrode active material artificial graphite, conductive agent (Super P), binder styrene butadiene rubber and thickener sodium carboxymethyl cellulose were dissolved in a deionized water solvent system according to a weight ratio of 98:0.5:1:0.5, and the mixture was stirred and mixed to obtain a negative electrode slurry. The negative electrode slurry was coated on a copper foil, dried, cold pressed and slit to obtain a negative electrode.
[0126] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92 is used as the electrolyte of the lithium ion battery.
[0127] The positive electrode, separator and negative electrode are stacked in order, with the separator placed between the positive and negative electrodes, and wound to obtain an electrode assembly. The electrode assembly is placed in an outer package, injected with electrolyte and packaged, and then formed into a final lithium-ion battery product.
[0128] 2. Test Method
[0129] 1. Modulus test of diaphragm
[0130] Testing instrument: DMA (Dynamic Mechanical Analyzer)
[0131] Test method steps: First, cut the diaphragm into a certain size (8mm×50 mm) and place it in the DMA test fixture; then, start the DMA modulus test program, and after the test is completed, the diaphragm temperature-modulus curve is obtained. Based on the temperature-modulus curve, the diaphragm modulus at a certain temperature can be read.
[0132] 2. Tensile strength test of adhesive
[0133] Place the adhesive film sample on the tensile test fixture of the universal testing machine and fix the fixture vertically. The universal testing machine applies stress to stretch the sample at a constant rate (20mm / min), causing the sample to stretch along the axial direction to produce tensile deformation until the sample breaks or fractures. Read the maximum load stress value Pmax (in N) applied by the universal testing machine, and calculate the tensile strength α of the adhesive using the following formula:
[0134] α=Pmax / (W×T),
[0135] Wherein W and T are the initial width and initial thickness of the adhesive film sample, respectively, and the unit of the initial width and initial thickness is mm.
[0136] 3. Melting temperature test of adhesive
[0137] Test instrument: DCS (differential scanning calorimetry);
[0138] Test method and steps: Take a certain amount (5-10mg) of adhesive film and place it in the crucible of the instrument. The instrument is heated at 10℃ / min to 30-50℃ above the melting extrapolation termination temperature to eliminate the thermal history of the material; then the instrument is cooled at 10℃ / min to 30-50℃ below the expected crystallization temperature; then heated at 10℃ / min to 30-50℃ above the melting extrapolation termination temperature, and the melting temperature is measured; compare the mass of the sample before and after the measurement, and repeat the above process if weight loss is found. Common test standards: ISO 11357-3-2011, ASTM E794-06 (2012), ASTMD3418-12 E1 、GB 19466.3-2004.
[0139] Melting temperature calculation: After the test is completed, the DSC absorption curve is obtained. Since the melting temperature range of the polymer binder is relatively wide, the entire melting process may be accompanied by a complex melting / recrystallization / crystal adjustment process. Therefore, the melting temperature of the polymer binder is usually taken as the absorption peak temperature.
[0140] 4. Determination of metal elements and their content ratio in adhesives
[0141] The battery was disassembled in a glove box, the diaphragm was taken out and the PVDF / PMMA adhesive layer coated on the porous coating was removed, leaving the porous coating, and then the porous coating was redispersed in water by "water washing". After centrifugal separation of inorganic particles, a water washing liquid was obtained, which included a binder. The water washing liquid was measured by inductively coupled plasma (ICP) testing to obtain the metal elements in the binder and their content ratios.
[0142] 5. Specific surface area test of inorganic particles
[0143] Start the test software, take a certain amount of inorganic particles and place them in the sample test chamber, and use the BET specific surface area determination method to test the specific surface area of the inorganic particles. After the test is completed, the test software automatically reads the specific surface area value of the inorganic particles.
[0144] 6. Particle size test of inorganic particles
[0145] Start the test software, place the inorganic particles that meet the test quality requirements in the test chamber of the Malvern 3000 laser particle size analyzer, and then start ultrasound for 5 minutes to ensure that the particles are not agglomerated. Then enter the particle size test step, and the software outputs the particle size distribution curve.
[0146] 7. Thermal shrinkage test of diaphragm in MD and TD directions
[0147] First, the diaphragm was cut into a size of length MD1 and width TD1 (MD1 = 10 cm, TD1 = 5 cm) to obtain a test diaphragm sample. Secondly, the cut diaphragm sample was placed between two A4 papers and baked in a 150°C oven for 1 hour. Then, a CCD camera was used to measure the length and width of the diaphragm sample after baking at 150°C for 1 hour, which were recorded as MD2 and TD2, respectively. Finally, the thermal shrinkage rate L1 of the diaphragm in the MD direction and the thermal shrinkage rate L2 of the diaphragm in the TD direction were calculated by the following formula:
[0148] L1 = (MD1-MD2) / MD1;
[0149] L2 = (TD1 - TD2) / TD1.
[0150] 8. Thickness test of diaphragm, substrate and porous coating
[0151] The thickness of the substrate and the diaphragm were measured using a benchtop diaphragm thickness gauge and recorded as H1 μm and Hμm, respectively. The thickness of the porous coating H2μm was calculated using the following formula:
[0152] H2=H-H1.
[0153] 9. Adhesion test of porous coating
[0154] First, lay the coated diaphragm sample flat on the glass plate, keep the porous coating facing up, and fix the four sides with tape to ensure that the diaphragm is flat and fixed on the glass plate; secondly, use the special tape for peeling force test to stick it flatly on the surface of the porous coating; then, use a 1KG pressure roller to roll back and forth on the pasting area of the special tape for peeling force test; then, cut out a 15mm×54.2mm diaphragm test sample in the pasting area of the special tape for peeling force test; finally, fix one side of the diaphragm test sample on one end of the high-speed rail tensile testing machine, and fix the tape side on one end of the moving bracket of the high-speed rail tensile testing machine. The moving bracket stretches the tape at a certain speed so that the tape is peeled off 180° from the diaphragm surface. The value read by the test software is the adhesion of the porous coating.
[0155] 10. Air permeability test of porous coating
[0156] Test instrument: Gurley air permeability meter
[0157] Test method and steps: First, take a substrate of a certain size (5x5 cm) and place it on the air permeability test platform to measure the air permeability of the substrate G1 s / 100ml; then, take a membrane of a certain size (5x5 cm) coated with a certain thickness of porous coating and place it on the air permeability test platform to measure the air permeability of the substrate G2 s / 100ml.
[0158] The air permeability G3 of the porous coating is calculated as: G3 = G2 - G1, which is the air permeability of the porous coating.
[0159] The substrate of the porous coating diaphragm is the same as the substrate of the test substrate air permeability. The porous coating air permeability test generally tests 6 parallel samples and takes the average value;
[0160] 11. Diaphragm thickness test after baking at 150℃ for 1 hour
[0161] The diaphragm was placed in an oven at 150°C and baked for 1 hour, and the diaphragm was cut with an ion beam cutter to form a cross section; subsequently, the thickness of the diaphragm cross section was measured using a scanning electron microscope, which was the thickness of the diaphragm after baking at 150°C for 1 hour.
[0162] 12. Hot box test
[0163] Take 100 lithium-ion battery samples, charge them to 4.5V at a constant current of 0.5C at room temperature, and further charge them at a constant voltage of 4.5V until the current is less than 0.05C, so that they are in a fully charged state of 4.5V. Put the lithium-ion battery samples in an oven and place them at 137℃ for 1 hour. If the lithium-ion battery does not smoke, catch fire or explode, it is recorded as passed, otherwise it is recorded as failed. The hot box pass rate refers to the ratio of the number of lithium-ion batteries that pass the test to the total number of lithium-ion batteries.
[0164] 13. Nail penetration test
[0165] First, check the appearance of the battery and take photos before and after the nail penetration test; second, stick the temperature sensing wire to the center of the battery surface; then, place the test battery on the test table in a 20±5℃ test environment, and use a 2.5mm diameter steel nail to test from the center of the sample at a speed of 150mm / s, and completely pierce the sample; if the battery does not catch fire or explode, it means that the battery has passed the test.
[0166] 3. Test Results
[0167] Table 1 shows the effect of the pH value of the binder on the properties of the separator and the electrochemical properties of the lithium-ion battery, where the thickness of the porous coating is 3.0 μm; the porous substrate component is PE and the thickness is 6.0 μm.
[0168] As can be seen from Table 1, compared with the comparative example, in the embodiment, by adjusting the pH values of the first binder and the second binder to satisfy 7≤pH1≤11 and 3≤pH2≤7 respectively, and the ratio pH1 / pH2 satisfies 1≤pH1 / pH2≤3.6, (1) a binder with greater tensile strength and higher melting temperature can be obtained; (2) after being baked at 150°C for 1 hour, the thickness of the diaphragm in the embodiment is smaller and the MD and TD thermal shrinkage rates are lower; (3) all the electrochemical devices in the embodiment pass the hot box test and the nail penetration test. After being baked at 150°C for 1 hour, for the diaphragm described in the embodiment, during the heating process, the substrate and the porous coating are integrated, so the thickness of the diaphragm after heating is less than the initial diaphragm thickness. In contrast, the diaphragm described in the comparative example shrinks severely at high temperatures, and many ridges / protrusions appear on the surface, resulting in the thickness of the diaphragm after heating being greater than the initial diaphragm thickness.
[0169] Table 2 is an improvement on Example 1-1, and the only difference is that the content of the first binder and the second binder is different. From the data in Table 2, it can be seen that by further adjusting the content of the first binder and the second binder to meet 0.2≤w1≤4, 2≤w2≤8, and 0.025≤w1 / w2≤2, the tensile strength of the binder, the thermal stability of the separator, and the safety performance and cycle stability of the electrochemical device can be further improved.
[0170] Table 3 is an improvement on Example 1-1, the only difference being the type and content of the metal element added to the first binder. As shown in Table 3, compared with adding only one metal element, the tensile strength of the binder, the thermal stability of the diaphragm, and the safety performance and cycle stability of the electrochemical device are further improved after adding two metal elements. In addition, it can be seen that adding metal elements with different valences to the first binder further improves the performance of the binder, the diaphragm, and the electrochemical device.
[0171] It can be seen from Table 3 that when the content ratio a of the metal element with a valence of +1 to the metal element with a valence of +2 is in the range of 1≤a≤10, the performance of the binder, the diaphragm and the electrochemical device can be further improved; when the content ratio b of the metal element with a valence of +1 to the metal element with a valence of +3 is in the range of 1≤b≤50, the performance of the binder, the diaphragm and the electrochemical device can be further improved.
[0172] Table 4 is an improvement on the basis of Examples 3-9, the only difference being the composition, median particle size and content of the inorganic particles. It can be seen from Examples 3-9 to 4-5 that the use of aluminum oxide, boehmite, zirconium oxide, boron nitride, silicon nitride or aluminum nitride as the inorganic particles in the porous coating can produce a diaphragm and an electrochemical device with excellent high temperature performance.
[0173] It can be seen from Examples 4-6 to 4-12 that when the median particle size Dv50 of the inorganic particles satisfies 0.3 μm ≤ Dv50 ≤ 2 μm, a diaphragm and an electrochemical device with better high temperature performance can be obtained.
[0174] It can be seen from Examples 4-13 to 4-18 that when the weight content m1% of the inorganic particles satisfies 90≤m1≤96 based on the total weight of the porous coating, a separator and an electrochemical device with better high temperature performance can be obtained.
[0175] Table 5 is an improvement on the basis of Example 3-9, the only difference being the composition and content of the wetting agent. It can be seen from Examples 3-9 to 5-3 that the use of polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer or siloxane as the wetting agent in the porous coating can obtain a diaphragm and an electrochemical device with excellent high temperature performance.
[0176] It can be seen from Examples 5-3 to 5-7 that, based on the total weight of the porous coating, when the weight content m3% of the wetting agent satisfies 0.5≤m3≤1.5, a diaphragm and an electrochemical device with better high temperature performance can be obtained.
[0177] Table 6 is an improvement on the basis of Example 3-9, the only difference being the thickness of the porous coating and the porous substrate. It can be seen from Examples 3-9 to 6-6 that when the thickness H2 of the porous coating is in the range of 0.5≤H2≤4, a diaphragm and an electrochemical device with better high temperature performance can be obtained. It can be seen from Examples 6-7 to 6-13 that when the thickness H1 of the porous substrate is in the range of 3≤H1≤10, a diaphragm and an electrochemical device with better high temperature performance can be obtained.
[0178] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.
[0179] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
[0180] Table 1
[0181]
[0182]
[0183]
[0184]
[0185] Table 2
[0186]
[0187]
[0188] Table 3
[0189]
[0190]
[0191]
[0192] Table 3
[0193]
[0194]
[0195] Table 4
[0196]
[0197]
[0198] Table 5
[0199]
[0200] Table 6
[0201]
Claims
1. A diaphragm, comprising: A porous substrate and a porous coating, wherein the porous coating is disposed on at least one surface of the porous substrate, the porous coating comprises inorganic particles and a binder, the binder comprises a first binder, the first binder comprises a metal element, wherein the modulus of the separator at a temperature T is P, T is 150°C, 10 8 Pa≤P≤10 9 Pa; The metal elements include at least two of Li, Na, Ca, Mg or Al.
2. The diaphragm according to claim 1, wherein The tensile strength of the adhesive is αMPa, 0.5≤α≤30.
3. The diaphragm according to claim 1, wherein The melting temperature of the binder is T f ℃, 150≤T f ≤250.
4. The diaphragm according to claim 1, wherein The metal element includes at least one of metal elements having a valence of +1, +2 or +3.
5. The diaphragm according to claim 1, wherein The adhesive further includes a second adhesive.
6. The diaphragm according to claim 5, wherein The binder satisfies one of the following conditions: (a) based on the total weight of the porous coating layer, the weight contents of the first binder and the second binder are w1% and w2%, respectively, wherein 0.2≤w1≤4, 2≤w2≤8, and 0.025≤w1 / w2≤2; (b) The pH value of the first binder is pH1, the pH value of the second binder is pH2, 7≤pH1≤11, 3≤pH2≤7, 1≤pH1 / pH2≤3.
6.
7. The diaphragm according to claim 5, wherein: The second binder satisfies one of the following conditions: (c) based on the total weight of the porous coating layer, the weight content w2% of the second binder satisfies 2≤w2≤8; or (d) The pH value pH2 of the second binder satisfies 3≤pH2≤7.
8. The diaphragm according to claim 1, wherein The first binder satisfies one of the following conditions: (e) the first binder contains only the metal element with a valence of +1 and the metal element with a valence of +2, wherein the molar content ratio of the metal element with a valence of +1 to the metal element with a valence of +2 is a, 1≤a≤10; (f) The first binder contains only the metal element with a valence of +1 and the metal element with a valence of +3, wherein the molar content ratio of the metal element with a valence of +1 to the metal element with a valence of +3 is b, 1≤b≤50.
9. The diaphragm according to claim 5, wherein: At least one of the first binder and the second binder includes a carboxyl group and / or a sulfonic acid group.
10. The diaphragm according to claim 5, wherein The binder satisfies at least one of the following conditions: (g) the first binder comprises at least one of the following: sodium polymethylcellulose, lithium polymethylcellulose, lithium polycarboxymethylcellulose, lithium polyhydroxypropyl methylcellulose, calcium polyacrylate, lithium polyacrylate or calcium polymethacrylate; (h) The second binder includes at least one of the following: polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate, polymethyl methacrylate or styrene-butadiene rubber.
11. The diaphragm according to claim 1, wherein The specific surface area of the inorganic particles is S BET m 2 / g,2≤S BET ≤10.
12. The diaphragm according to claim 1, wherein The median particle size Dv50 of the inorganic particles satisfies 0.3 μm≤Dv50≤2 μm.
13. The diaphragm according to claim 1, wherein The inorganic particles include at least one of the following: aluminum oxide, boehmite, zirconium oxide, boron nitride, silicon nitride or aluminum nitride.
14. The diaphragm according to claim 1, wherein The porous coating also includes a wetting agent, wherein, based on the total weight of the porous coating, the weight content of the inorganic particles is m1%, the weight content of the binder is m2%, and the weight content of the wetting agent is m3%, wherein 90≤m1≤96, 3≤m2≤9, 0.5≤m3≤1.5, and m1+m2+m3=100.
15. The diaphragm according to claim 14, wherein The wetting agent includes at least one of the following: polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer or siloxane.
16. The diaphragm according to claim 1, wherein The separator is placed at 150° C. for 1 hour, and the thermal shrinkage rate of the separator in the MD direction is L1, and the thermal shrinkage rate in the TD direction is L2, L1<10%, L2<10%, and 0.75≤L1 / L2≤1.
2.
17. The diaphragm according to claim 1, wherein The diaphragm satisfies at least one of the following conditions: (i) the thickness of the diaphragm is H μm, 3.5≤H≤14; (j) the thickness of the porous substrate is H1 μm, 3≤H1≤10; or (k) The thickness of the porous coating layer is H2 μm, 0.5≤H2≤4.
18. The diaphragm according to claim 1, wherein The porous coating satisfies at least one of the following conditions: (l) The bonding force of the porous coating is FN / m, 5≤F≤100; (m) The air permeability of the porous coating is K s / 100 ml, 5≤K≤40.
19. An electrochemical device comprising the separator according to any one of claims 1 to 18.
20. An electronic device comprising the electrochemical device according to claim 19.